EFFECT OF A TETRAHYDROISOQUINOLINE DERIVATIVE ON HEMATOLOGICAL PARAMETERS IN VIVO (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
At present, the evaluation of the safety and efficacy of newly developed biologically active compounds is one of the most pressing issues in pharmacology and experimental medicine. In particular, studying the effects of newly synthesized compounds on hematological parameters is of great importance for assessing their potential toxicity. Isoquinoline derivatives exhibit a wide range of pharmacological activities; however, their effects on the organism have not yet been sufficiently investigated. Therefore, determining the influence of the isoquinoline derivative TGIX-Cl on the formed elements of blood is considered highly relevant.